The Impact of Tobacco Policy Reforms on Smallholder Prices in Malawi. (January 2014) - Mkwara, Bentry; Marsh, Dan
<x xml:space="preserve">Abstract</x> Two key questions are addressed in this article. (i) Have Malawi's tobacco‐policy reforms led to improvements in the absolute prices that smallholders get? (ii) How do the prices that smallholders receive compare with what the rich estate owners get? Empirical results indicate that the reforms have led to some improvements in both absolute and relative prices that smallholder farmers receive. Major positive changes in the tobacco price‐structure have occurred after removing monopsony and liberalising the market. However, farmers, especially smallholders, are still faced with high transaction and logistics costs that need to be addressed.